Grand Papa and Ellen Aroon being an account of some of the happy times spent together by Thomas Jefferson and his favorite granddaughter - Monjo, F. N. (Dell Publishing, 1974)
Nine-year-old Ellen Wayles Randolph describes her relationship with her grandfather, Thomas Jefferson.